The London congestion charging scheme, 2003-2006 - Santos, G (Edward Elgar, 2008)
This chapter assesses the London Congestion Charging Scheme (LCCS). A brief overview of how the scheme works is given in Section 2 and a summary of its impacts on traffic is described in Section 3. With information and data from Transport for London demand elasticities are estimated in Section 4 and the area marginal congestion costs are described in section 5. Finally, a description and potential impacts of the Western Extension are presented in Section 6 and Section 7 concludes.